PENERAPAN MEDIA PEMBELAJARAN SCPB (SMART CARD PAHLAWAN BANGSA) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MATA PELAJARAN IPS SISWA KELAS VI SDN 01 NAMBANGAN LOR - Indriani, Anita; Parji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In elementary schools, Social Studies (IPS) plays a crucial role in instilling knowledge about socioeconomic and historical aspects of life, while developing critical thinking skills to understand surrounding social events. However, current instruction remains conventional and relies heavily on rote memorization. Consequently, students remain passive and struggle to explain cause-and-effect relationships or summarize materials when facing analytical questions. This results in low critical thinking and poor learning outcomes, with initial data showing 74% of sixth-grade students scoring below the Minimum Competency Criterion (KKM). To address this, the study utilized the SCPB (Smart Card Pahlawan Bangsa) medium to improve students' critical thinking and learning outcomes. This Classroom Action Research (PTK) was conducted in two cycles—planning, acting, observing, and reflecting. The subjects were 27 sixth-grade students at SDN 01 Nambangan Lor during the 2025/2026 academic year. Data collected through observation sheets and evaluation tests were analyzed qualitatively and quantitatively. Critical thinking was measured using a Likert-scale checklist, while learning outcomes were evaluated via class averages. The results demonstrated significant improvement: critical thinking skills increased from 33% in the pre-cycle to 70% in Cycle I, reaching 100% in Cycle II. Student learning outcomes also improved, rising from 26% in the pre-cycle to 55% in Cycle I, and ultimately achieving 93% in Cycle II. These findings confirm that integrating SCPB effectively enhances critical thinking and learning outcomes in the IPAS program.